The Relationship between Pre-service Primary School Teachers' Perception of 21st-Century Skills, Mathematical Literacy Self-Efficiency, and Financial Literacy Attitudes and Behaviors - Ahmet Oguz Akcay; Muhammed Serhat Semercioglu; Hasan Güllü (Universitas Pendidikan Indonesia, 2022)
Primary school teachers are one of the main actors in basic education. In this context, their 21st-century skills, math literacy, and financial literacy affect the quality of their teaching. This study aims at examining the relationship between pre-service primary school teachers' mathematical literacy, 21st-century skills, and financial literacy levels. This study used a relational survey model, and the study group involved a total of 276 pre-service primary school teachers. “Mathematical Literacy Self-Efficacy Scale,” “21st-Century Skills Efficacy Perceptions Scale,” and “Financial Literacy Attitude and Behavior Scale” were used in the study. The results showed that pre-service primary school teachers' perceptions of 21st-century skills efficiency were high, the mathematical literacy self-efficacy of the pre-service primary school teachers was above the average, and the pre-service primary school teachers' financial literacy attitude and behavior levels were low. Also, a positive and significant relationship was found between the mathematical literacy self-efficacy of pre-service primary school teachers and their perceptions of 21st-century skills efficiency. In addition, a negative and significant correlation was found between the mathematical literacy self-efficacy of the pre-service primary school teachers and their financial literacy attitudes and behaviors.